Human Capital and Economic Growth in Latin America: A Cointegration and Causality Analysis - Osiobe, Ejiro U (The Economics and Finance Letters, 2020)
This paper investigates the causal relationship between government spending on education and economic growth in eight selected Latin American countries by using panel unit root test and panel cointegration analysis for the period 2000-2014. A three-variable model was formulated with trade volume as the second independent variable. The findings conclude that government spending on education and economic growth in the selected countries is positively and significantly associated, in the long and short-run, with evidence of a bidirectional Granger causal relationship between the dependent and the variable of interest, a unidirectional Granger causal relationship between trade volume and economic growth. The implication of our results shows that government secondary school spending on education has a positive impact on the selected countries, and our analysis can be replicated with other countries.